Desenvolvimento de um sistema de produção recombinante de uma cistatina em uma linhagem industrial de Saccharomyces cerevisiae - Nakayama, Darlan Gonçalves (2011)
Saccharomyces cerevisiae is the most important microorganism used in alcoholic fermentation process. A strain of Saccharomyces cerevisiae widely used to produce alcohol in Brazil is the PE-2, due to its high fermentation capacity. The goal of this study was to develop an expression system for recombinant proteins using the industrial strain of Saccharomyces cerevisiae, PE-2. The protein chosen to be used as a model for this system was the Cane-CPI-1, an inhibitor of cysteine protease. Initially the construction of plasmids containing CaneCPI-1 gene was performed and yeast cells were transformed with pYADE4-CaneCPI-1 construction. The transformed strain was submitted to expression analyses during batch fermentative process with cell recycle. The recombinant protein was expressed in yeast cells and it was possible to purify the recombinant protein by affinity chromatography on nickel column. This purified protein was immunodetected using a polyclonal anti-CaneCPI-1antibody and monoclonal anti His-Tag antibody, which were also able to detect the CaneCPI-1 in a crude extract from Saccharomyces cerevisiae cells. Assays of inhibitory activity performed with the purified CaneCPI-1 revealed its ability to inhibit the catalytic activity of a cysteine proteinase. This study showed that the use of transformed strain did not affect the fermentation process and that the PE-2 industrial strain of S. cerevisiae can be a viable expression system for recombinant protein production and open perspectives for production of any protein of biotechnological applications during fermentation alcoholic process.